Accounting Practices in Small Enterprise Financial Growth Sustainability (gjstudies, 2025)
This research investigates the underexplored intersection of formal accounting practicesand the long-term financial growth sustainability of small enterprises, positing that conventional accounting frameworks are insufficient for capturing the unique, non-linear growthtrajectories of such entities. Departing from traditional financial analysis, we introducea novel methodological framework termed ’Resilience-Accounting Integration’ (RAI), whichsynthesizes principles from ecological resilience theory, complexity economics, and behavioralfinance into a cohesive accounting practice. The RAI framework moves beyond static balance sheets and profit-and-loss statements to incorporate dynamic metrics of financial buffercapacity, adaptive transaction cycles, and stakeholder trust capital—dimensions typicallyabsent from standard ledgers. Our methodology employs a longitudinal, mixed-methodsapproach, combining qualitative ethnographic case studies of twelve small enterprises overa three-year period with the development and application of a quantitative Resilience IndexScore (RIS). The findings reveal a significant positive correlation (r = 0.78, p ¡ 0.01) betweenthe adoption of RAI-informed practices and sustained financial growth through periods ofmarket volatility. Crucially, the study identifies ’narrative coherence’ in financial reporting—the alignment of internal accounting narratives with strategic action—as a strongerpredictor of sustainable growth than mere profitability metrics. This research contributesoriginal insights by reframing accounting not as a passive recording tool but as an active,strategic architecture for building financial resilience, offering a new paradigm for small enterprise management that prioritizes adaptive capacity and systemic health over short-termfiscal optimization